APPLICATION OF ATTRIBUTE BASED COSTING TECHNIQUE TO REDUCE COSTS - Dr. Mohammed Oleiwi; Al chlaihawi (Scholar Express Journals, 2023)
As a result of the rapid technological progress, the increased intensity of competition, and the global openness of markets, this led to the invasion of the local markets with large numbers of foreign products of better quality compared to local products, which exposed the Iraqi economic units to many pressures for various reasons, the most important of which is the high cost of their products and the low level of quality, which requires These units search for solutions that lead to providing a high-quality product that is able to compete with the foreign product in terms of price and quality, and then achieve satisfaction. Therefore, the research aims to apply cost technology based on specifications and explain its role in reducing product costs and applying it in one of the industrial economic units. In order to achieve the goal of the research, the researcher relied on the data of the economic unit, the research sample, as well as personal interviews and field visits to the economic unit. The researcher reached a set of conclusions, the most important of which are: The weakness of the costing system applied in the research sample factory and its shortcomings in accurately following up and counting the cost elements during the product life cycle.
Keywords: Attribute Based Costing; costs reduction